Emergency Department Management of Childhood Pneumonia in the United States Prior to Publication of National Guidelines. (20th March 2013) - Neuman, Mark I.; Shah, Samir S.; Shapiro, Daniel J.; Hersh, Adam L.
Abstract Background Recent publication of national guidelines by the Pediatric Infectious Diseases Society (PIDS) and the Infectious Diseases Society of America (IDSA) provide recommendations around diagnostic testing and antibiotic treatment for children with community‐acquired pneumonia (CAP). These guidelines emphasize limited use of chest radiograph (CXR) and complete blood count (CBC) and routinely performing viral testing and use of narrow‐spectrum antibiotics. Objectives The objective was to estimate the rate of emergency department (ED) visits for pediatric CAP in the United States and to describe management of patients prior to publication of consensus national guidelines. Methods Data were obtained from the National Hospital Ambulatory Medical Care Survey (NHAMCS) for ED visits from 2001 through 2009 for children with CAP. Results During the study period there were an estimated 375, 000 ED visits for CAP annually; 85% occurred within a general, rather than pediatric, ED. Overall, 20% of children with CAP were hospitalized. Among children discharged from EDs with CAP, CBC was performed during 30% of visits, CXR during 83%, and viral testing in only 13%. Twelve percent of children discharged from EDs with CAP had blood cultures obtained. No major differences were observed in the rates of laboratory testing or antibiotic administration between children treated in general versus pediatric EDs. During the study period, only 21% of children discharged from EDs with CAP received amoxicillin, the guideline‐recommended antibiotic. Conclusions Most ED visits for CAP in the United States occur in general EDs. To encourage care that is consistent with national guidelines, efforts should be made to reduce the performance of certain diagnostic testing, such as CBC and CXR, among children discharged from EDs with CAP. Additionally, the use of narrow‐spectrum antibiotics should be encouraged.